Rocking Wall Street : - Marks, Gary. (Wiley, 2007)
"A true Renaissance man and teacher, Gary Marks adeptly explores four investment strategies that can achieve strong results and peace of mind-two concepts usually considered mutually exclusive in the world of Wall Street investing. Using his vast experience and folksy storytelling, Gary provides lessons, anecdotes, and strategies that will help readers find multiple levels of success." —Mitch Levine Founder and CEO, Enable Capital Management